2017
DOI: 10.1103/physrevb.95.024509
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity on a quasiperiodic lattice: Extended-to-localized crossover of Cooper pairs

Abstract: We study a possible superconductivity in quasiperiodic systems, by portraying the issue within the attractive Hubbard model on a Penrose lattice. Applying a real-space dynamical mean-field theory to the model consisting of 4181 sites, we find a superconducting phase at low temperatures. Reflecting the nonperiodicity of the Penrose lattice, the superconducting state exhibits an inhomogeneity. According to the type of the inhomogeneity, the superconducting phase is categorized into three different regions which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 56 publications
4
60
0
5
Order By: Relevance
“…One of the simplest ones with geometrical quasiperiodicity is the Penrose lattice in two dimensions [9][10][11][12][13][14][15][16][17]. On this lattice, a few strongly correlated models have been studied: the Ising model for classical spins [18][19][20], the Heisenberg model for quantum spins [21,22], and the Hubbard [23,24] and Anderson lattice models [25,26] for correlated electrons. One important feature of the Penrose lattice is the presence of thermodynamically degenerate oneparticle states, and they are called confined states, since the their wave functions are strictly confined in a finite region in space [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the simplest ones with geometrical quasiperiodicity is the Penrose lattice in two dimensions [9][10][11][12][13][14][15][16][17]. On this lattice, a few strongly correlated models have been studied: the Ising model for classical spins [18][19][20], the Heisenberg model for quantum spins [21,22], and the Hubbard [23,24] and Anderson lattice models [25,26] for correlated electrons. One important feature of the Penrose lattice is the presence of thermodynamically degenerate oneparticle states, and they are called confined states, since the their wave functions are strictly confined in a finite region in space [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 23, we found that, even without a Fermi surface, there exists a superconducting state with spatially extended Cooper pairs in a weak-coupling regime of the attractive Hubbard model. This Cooper pairing cannot be straightforwardly captured by Bardeen-Cooper-Schrieffer picture in the sense that the latter is based on a description in a momentum space absent in quasiperiodic systems.…”
mentioning
confidence: 99%
“…Eventually, above h c2 0.85 the normal phase appears. Note that, unlike in periodic systems, the superconducting state in quasiperiodic systems is always inhomogeneous with respect to the amplitude of ∆ i even without magnetic field [23] while its phase (sign) is uniform. The finding here is an inhomogeneous sign structure in the superconducting state, which emerges under the magnetic field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Também mostram que a supercondutividade neste tipo de sistema parece ser convencional 43 e estudos teóricos corroboram com a afirmativa. 44 Também há proposição de estados superfluidos, 45 mas ainda não foi relatada uma realização experimental.…”
Section: Introductionunclassified